When the Sea Speaks: Nature’s Power and Presence in Emily Dickinson’s Poetic Imagination - Khanal, Dhiraj (NPRC Journal of Multidisciplinary Research, 2025)
Emily Dickinson’s poetry reveals an ecocritical consciousness in its treatment of nature, particularly the sea, as an autonomous force challenging human dominance. While scholars have widely examined her themes of death and immortality, her naval imagery remains underexplored from an ecocritical viewpoint. This study analyzes how Dickinson’s sea poems present nature as an autonomous entity resisting anthropocentric interpretation, anticipating modern environmental thought. Bridging Dickinson’s poetry with ecocritical theory, this research demonstrates how her works destabilize Romantic nature representations by portraying the sea as a sublime, incomprehensible force. Unlike conventional representations of nature as passive or symbolic, Dickinson’s nautical imagery asserts ecological agency, aligning with contemporary critiques of human-centered worldviews. Through close reading of key naval poems, this study establishes the sea’s autonomy in Dickinson’s work, examines her critique of human-nature hierarchies, and contextualizes her vision within ecocritical theory. This perspective offers new insights into both Dickinson’s ecological vision and current ecological discourse, highlighting its relevance in an age of environmental crisis.